2012
DOI: 10.3892/ol.2012.578
|View full text |Cite
|
Sign up to set email alerts
|

WT1 silencing by RNAi synergizes with chemotherapeutic agents and induces chemosensitization to doxorubicin and cisplatin in B16F10 murine melanoma cells

Abstract: Abstract. The Wilm's tumor gene (WT1), encoding a transcription factor that modulates the expression of certain genes that are involved in proliferation and apoptosis, is overexpressed in numerous solid tumors. WT1 is important for cell proliferation and in the diagnosis of melanoma. The objectives of this study were to investigate whether WT1 silencing is capable of synergizing with chemotherapeutic agents and whether this silencing is capable of sensitizing cancer cells to doxorubicin and cisplatin in the B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Wagner et al showed that inhibition of WT1 reduces cell proliferation, migration and vascular formation through transcriptional activation of the proto-oncogene ETS-1 [36]. A combination strategy of WT1 gene silencing and chemotherapeutic agents cisplatin and doxorubicin was found to have a synergistic effect on inhibiting cell proliferation in B16F10 murine melanoma cells [37]. In human melanoma, WT1 protein expression was found to be associated with shorter overall survival[38].…”
Section: Discussionmentioning
confidence: 99%
“…Wagner et al showed that inhibition of WT1 reduces cell proliferation, migration and vascular formation through transcriptional activation of the proto-oncogene ETS-1 [36]. A combination strategy of WT1 gene silencing and chemotherapeutic agents cisplatin and doxorubicin was found to have a synergistic effect on inhibiting cell proliferation in B16F10 murine melanoma cells [37]. In human melanoma, WT1 protein expression was found to be associated with shorter overall survival[38].…”
Section: Discussionmentioning
confidence: 99%
“…WT1 is supposed to act as a modulator of proliferation, a transcriptional activator and as a tumour suppressor 3 4. By regulating the antiapoptotic protein Bcl-xL, WT1 contributes to the resistance against apoptotic therapeutic strategies such as tumor necrosis factor α-related apoptosis-inducing ligand (TRAIL),5 and silencing of WT1 leads to increased tumour sensitivity to cisplatin chemotherapy 6…”
Section: Introductionmentioning
confidence: 99%
“…Down-regulation of WT1 protein expression by antisense oligodeoxynucleotides and RNA interference in different types of cell lines (1,(19)(20)(21) was found to result in cell growth inhibition, as well as modified expression of proteins involved in the cell cycle, such as cyclin D1, and those involved in apoptosis, such as caspase-3 and poly-ADPribose polymerase (1,19). In vivo, Zamora et al observed that delivery of complexes of small hairpin RNA plasmid against WT1 (shRNA-WT1) with polyethyleneimine (PEI) by an aerosol system to lungs of mice with B16F10 lung metastases resulted in a reduction in the number and size of lung tumor foci and the number and size of tumor blood vessels, suggesting reduced angiogenesis (22).…”
mentioning
confidence: 99%